Long-term outcomes following endovascular and surgical revascularization for peripheral artery disease: a propensity score-matched analysis. (24th February 2021) - Parvar, Saman L; Ngo, Linh; Dawson, Joseph; Nicholls, Stephen J; Fitridge, Robert; Psaltis, Peter J; Ranasinghe, Isuru
Abstract: Aims: Peripheral artery disease (PAD) revascularization can be performed by either endovascular or open surgical approach. Despite increasing use of endovascular revascularization, it is still uncertain which strategy yields better long-term outcomes. Methods and results: This retrospective cohort study evaluated patients hospitalized with PAD in Australia and New Zealand who underwent either endovascular or surgical revascularization between 2008 and 2015, and compared procedures using a propensity score-matched analysis. Hybrid interventions were excluded. The primary endpoint was mortality or major adverse limb events (MALE), defined as a composite endpoint of acute limb ischaemia, urgent surgical or endovascular reintervention, or major amputation, up to 8 years post-hospitalization using time-to-event analyses 75 189 patients fulfilled eligibility (15 239 surgery and 59 950 endovascular), from whom 14 339 matched pairs (mean ± SD age 71 ± 12 years, 73% male) with good covariate balance were identified. Endovascular revascularization was associated with an increase in combined MALE or mortality [hazard ratio (HR) 1.13, 95% confidence interval (CI): 1.09–1.17, P < 0.001]. There was a similar risk of MALE (HR 1.04, 95% CI: 0.99–1.10, P = 0.15), and all-cause urgent rehospitalizations (HR 1.01, 95% CI: 0.98–1.04, P = 0.57), but higher mortality (HR 1.16, 95% CI: 1.11–1.21, P < 0.001) when endovascular repair was compared to surgery. In subgroup analysis, these findings were consistent for both claudication and chronic limb-threatening ischaemia presentations. Conclusion: Although the long-term risk of MALE was comparable for both approaches, enduring advantages of surgical revascularization included lower long-term mortality. This is at odds with some prior PAD studies and highlights contention in this space. Graphical Abstract: